Peningkatan Kualitas Pembelajaran Guru Bahasa Inggris MTs Sabilurrrasyad NW Barabali Lombok Tengah Melalui Lesson Study For Community Learning (LSLC) - Henny Soepriyanti; I Made Sujana; Lalu Thohir; Edy Syahrial (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
The implementation of workshops and practice for the implementation of Lesson Study for Community Learning (LSLC) was held at MTs Sabilurrrasyad NW Barabali, Central Lombok. The purpose of this community service activity was to equip teachers at the school with the knowledge and practice of planning, implementing and evaluating interactive learning through LSLC. The outcome of this activity was the development of teachers’ pedagogical competence in implementing LSCL. Through this activity, it is hoped that these teachers can apply LSLC in their daily teaching and learning practices that are more accommodating to both teachers and students. The target audience for this workshop was the teachers of MTs Sabilurrrasyad NW Barabali, Central Lombok. The reason for the urgency of conducting this activity is that teachers in the target area lack training in developing teaching skills. They do not update their pedagogical skills. To accommodate the learning needs of andragogy, this workshop was conducted using the LSCL-style collaborative learning activity model, such as dialogue, problem solving, demonstration, problem analysis exercises without criticism, reflection and question and answer. Results of the training activity show that the workshop participants felt that they underwent substantial improvement in their pedagogical competence. They therefore expect that similar types of community services would be continued in the future, focusing on improving their professionalism. The participants revealed that they had learned much from the workshop of how to learn from others without criticism and unproductive arguments.